Treatment-Responsive Granulomatous-Lymphocytic Interstitial Lung Disease in a Pediatric Case of Common Variable Immunodeficiency - Robert Tillman; R. Paul Guillerman; Timothy Trojan; Manuel Silva-Carmona; Manuel Silva-Carmona; Ivan K. Chinn (Frontiers Media S.A., 2019)
Granulomatous-Lymphocytic Interstitial Lung disease (GLILD) is a granulomatous and lymphoproliferative condition occurring in ~25% of Common Variable Immunodeficiency (CVID) patients with the highest prevalence in the late teen to young adult years. GLILD was first described in adults and carries a poor prognosis with survival estimated to be reduced by half. Here we report a pediatric case of CVID-associated GLILD that presented with rapid deterioration over 3 months and responded to adult-based treatment with dual chemotherapeutic agents (rituximab and azathioprine), resulting in complete resolution of clinical findings and near complete resolution of radiologic findings. This case highlights the opportunity to achieve a favorable outcome in GLILD following appropriate diagnosis and therapy.